Pension refrom in Europe - "Holzamann, Robert.( ed.)" (Washington, 2003)
This text examines the political economy of pension reform, an area in the European policy debate where reform progress has been uneven. It attempts to discover the cause of this uneveness and contains contributions from scholars and practitioners in economics and political sciences.
Keywords: Old - age - pensions - Europe